2000
DOI: 10.2105/ajph.90.2.245
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with tympanostomy tube insertion among preschool-aged children in the United States

Abstract: OBJECTIVES: Recurrent and persistent otitis media is often treated by tympanostomy tube insertion to ventilate the middle ear and restore hearing. This study examined the factors that predict which children are most likely to receive tympanostomy tubes through 3 years of age. METHODS: Multiple logistic regression was conducted on data from a nationally representative sample of children (N = 8285). RESULTS: By 3 years of age, 6.8% of US children had tubes inserted. Logistic regression indicated that after contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(34 citation statements)
references
References 51 publications
4
29
1
Order By: Relevance
“…Among them, 2221 had tympanostomy tube insertion before the age of 8 or 9 years for a cumulative incidence of 0.393%. Compared to other reports, one study showed the tympanostomy tube insertion rate in United states was 6.8% before the age of 3 and another study revealed middle ear surgical procedure was 9% in Norway [41], [42]. The rate of tube re-insertion is about 20% to 50% [8][10], [43].…”
Section: Discussionmentioning
confidence: 84%
“…Among them, 2221 had tympanostomy tube insertion before the age of 8 or 9 years for a cumulative incidence of 0.393%. Compared to other reports, one study showed the tympanostomy tube insertion rate in United states was 6.8% before the age of 3 and another study revealed middle ear surgical procedure was 9% in Norway [41], [42]. The rate of tube re-insertion is about 20% to 50% [8][10], [43].…”
Section: Discussionmentioning
confidence: 84%
“…Insurance status, maternal education, daycare attendance, breastfeeding, and exposure to secondhand smoke have been associated with OM and, in some cases, specifically to OME 21,24 . Although we found significant associations between SES and indications for TT, we did not find significant associations for race/ethnicity, the presence of siblings at home, daycare attendance, or secondhand smoke exposure.…”
Section: 4 Discussionmentioning
confidence: 99%
“…54 One out of 15 children, or 6.8% of the population, had tympanostomy tubes placed before the age of 3 years. 55 The health care costs of tympanostomy tubes are enormous, at an estimated cost of $2200 per patient 56 for a total of nearly $1.5 billion annually in the United States.…”
Section: Recurrent Aom and Tympanostomy Tubesmentioning
confidence: 99%